'Let the Writers Write…': A Conversation with TOOFLY. Issue 2 (3rd April 2017) - Castillo, Maria 'TOOFLY'; Craig, Todd
Abstract: When thinking about elements of hip-hop culture, it becomes important to include cultural brokers and key practitioners in the conversation, so that the culture does not become divorced from the conversations about it. To talk about graffiti culture, one should include a graffiti artist. This interview is conducted with artist and veteran graffiti writer Maria 'TOOFLY' Castillo.